Understanding the teaching of biology at A level - Francis Black, A; Francis Black, A C (2005)
This research focuses on uncovering, from the perspectives of practitioners themselves, the practical knowledge and understanding that shapes three teachers' successful teaching of biology at A level. Adopting a case study approach, it investigates the ways in which these biology teachers characterise their successful teaching of the subject at A level. It also explores the subject matter knowledge and understanding that shapes and accounts for these characterisations without making assumptions about the nature of this knowledge. Data are collected through the non-participant observation of a connected series of the teachers' A level biology lessons as well as informant-style interviewing following the observed lessons. The findings suggest that the main aim of the teachers' successful teaching of biology at A level is to ensure their students achieve examination success. In light of this, their teaching can be characterised in terms of three central features. First, they believe that to achieve this aim their students only need to know the substantive dimension of biological knowledge - they do not consider knowing the syntactic dimension to be a prerequisite to examination success. Second, they believe that their students need to conceptualise this substantive biological knowledge in several patterned ways. Third, they believe that the best way to encourage their students to develop and retain these specific conceptualisations is by adopting carefully controlled and highly structured teacher-centred pedagogical strategies. The teachers' characterisations appear to be shaped and accounted for by specific conceptions of biology which provide an overall structure to substantive biological knowledge - a structure that is determined by various guiding principles. This research provides a first attempt to map out the practical knowledge and understanding that shapes the successful teaching of biology at A level from the perspectives of teachers themselves. The ways in which these teachers characterise their teaching differ significantly from the ways in which such teaching is described in most of the extant literature in science education on teaching and learning. This study suggests that the teachers, far from lacking in knowledge, skills and understanding, are highly skilled practitioners who respond to the local and national contexts in which they work and, taking account of these, shape their subject matter teaching accordingly such that their main aim - student examination success - is achievable. This study highlights the discrepancy between academic writing in science education on practice and practice itself. The thesis ends with a consideration of the implications of the study for the research agenda in science education, the school science curriculum and the curriculum for teacher education in both preparing and supporting the professional development of science teachers.